The relationship between preconception nutritional status and the incidence of anemia among pregnant women at the Jambesari Community Health Center - Jamiatul Hasanah; Janie Palupi (Institute of Accounting Research and Novation (IARN), 2026)
The prevalence of anemia among pregnant women in Indonesia remains high, reaching 51.9% in 2024. In Bondowoso Regency and the service area of the Jambesari Community Health Center, the prevalence of anemia is also relatively high, at 47.8% and 45.1%, respectively. One factor suspected to contribute to this condition is poor preconception nutritional status. To determine the association between preconception nutritional status and the incidence of anemia among pregnant women in the service area of the Jambesari Community Health Center, Bondowoso Regency. A quantitative analytical study using a cross-sectional design. A sample of 104 pregnant women in their second and third trimesters was selected using simple random sampling. Data were obtained from medical records and the Maternal and Child Health registry, then analyzed using the chi-square test (0.05). Results: A total of 55.8% respondents had CED, while 44.2% respondents did not have CED. The majority of respondents did not have anemia 55.8%, while 33.7% had mild anemia and 10.6% had moderate anemia. The results of the chi-square test indicate that there is a significant association between preconception nutritional status and the incidence of anemia in pregnant women. Pregnant women with CED nutritional status are at higher risk of developing anemia than those without CED. Continuous efforts to improve preconception nutritional status through education and early detection are essential to prevent maternal anemia. These findings provide evidence for strengthening preconception nutritional screening and counseling at primary health care centers as part of maternal health services to improve pregnancy outcomes.